A factor-augmented vector autoregression (FAVAR) model for monetary policy analysis in Nigeria - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2014)
The study examines the impacts of monetary policy shocks on key macroeconomic variables using large dataset available to the Central Bank of Nigeria.
Includes bibliographical references.
oif 07/03/17
Loans
Keywords: Macroeconometric modeling; Monetary policy; Econometrics; Nigeria